Analyzing and Improving Flexural and Impact Strength of Composites Enhanced with Nanoparticles and Natural Fibers - Hossein Taghipoor; Jaber Mirzaei (Mechanics of Advanced Composite Structures)
One of the enormous challenges of bio-composites is the improvement of the flexural and impact strength. Therefore, the optimization and parametric investigation of nanocomposites reinforced with natural hybrid fibers is the main focus of this study. Kenaf/basalt/nanographene fibers in polypropylene were used to reinforce bio-composite specimens. Response Surface Method (RSM) was applied to study and present a mathematical model for the performance of bio-composite according to a number of parameters including the basalt fiber weight percentage, kenaf fiber as well as nanographene. The performance of the specimens was discussed under the bending and impact tests and the outcomes were explained by the use of FESEM images. The optimal value of the parameters was set as a multi-objective according to the increase of the flexural strength and energy absorption, the reduction of the specimens’ weight, and also a Pareto diagram was illustrated considering the design goals. The findings revealed that the composite specimen with the best flexural behavior had the flexural strength of 51.2558 MPa, which consisted of 0.8723 wt% of basalt fibers, 15% of kenaf fibers, and 0.76881% of graphene nanoparticles. In addition, the best specimen in terms of impact had 116,809 J / m energy absorption, which included 8.23% basalt fibers, 0.808% graphene nanoparticles, and 15% kenaf fibers.